Saint Francis And The "Canticle Of The Creatures" - Kijas, Zdzisław Józef (Miscellanea francescana, 2025)
Franciscan historians place the substantial composition of the Canticle of the Creatures in the spring of the year 1225 at San Damiano in Assisi. Suffering and illness, his increasingly weak eyesight and body, although they caused him suffering, allowed Francis to better perceive the presence and action of God in everything. Until then he had lived like a blind man, seeing only himself, his own incapacity and inability, his false greatness. But now, having lost his physical strength, he turned with ever greater intensity to the One on whom he felt increasingly dependent. It was in those conditions that he composed the Canticle of the Creatures, a poem about a great victory, the most beautiful and joyful song ever written by a mortal in praise of God, Creator of the Universe. An apparent weakness of the body and of the means, generate exceptional, particular, spirit-filled, immortal works. The lack of physical strength had made Francis a visionary. He could see beyond, deeper, he could see what was hidden from others. The Canticle of the Creatures is then not only a poetic song but a source of hope for those who suffer, those who feel weak, incapable, etc. Even then he can do many beautiful things on condition of being united with God.